Individual and Community-Contextual Level Factors Associated With Wellbeing Among Older Adults in Rural Zambia - Andrew Banda; Andrew Banda; Jaco Hoffman; Jaco Hoffman; Vera Roos (Frontiers Media S.A., 2024)
Objective: This article aims to identify individual and community-contextual level factors associated with the wellbeing of older adults (50 years and older) in rural Zambia.Methods: Data from the nationally representative 2015 Living Conditions Monitoring Survey (LCMS) was used. Employing multilevel mixed effects, the individual and community-contextual factors on wellbeing were determined.Results: Overall, 31.7% of rural older adults perceived their wellbeing as good. Both individual and community-contextual level factors are associated with the wellbeing of older adults in rural communities. At the individual level, wellbeing was associated with higher education attainment. Community-contextual factors significantly associated with wellbeing included improved housing, access to piped tap water within the premises, own charcoal or income to purchase firewood.Conclusion: The findings foreground the imperative to analyse both individual and community-contextual level factors of wellbeing to generate and present evidence for investments in education across the life course and for the development of infrastructure towards increasing the wellbeing of rural older adults. Additionally, the results provide a basis for planning by devising policies and programmes for older people to thrive and for no one to be left behind regardless the setting.